Organic ionic gel with high ionic conductivity, stretchability and long phosphorescence lifetime based on anion induced phase separation strategy as well as preparation and application of organic ionic gel

By adopting anion-induced phase separation strategy in ion gels, organic ion gels with high ionic conductivity, stretchability and long phosphorescence lifetime were prepared, which solved the problems of poor mechanical properties and short phosphorescence lifetime of existing phosphorescence materials, achieved the coordinated improvement of mechanical properties and phosphorescence performance, and was suitable for a variety of high-performance applications.

CN119775591AActive Publication Date: 2025-04-08UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411475223.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-04-08
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The existing phosphorescent materials have poor mechanical properties, instretchability and short phosphorescence lifetime, making it difficult to achieve synergistic improvements in mechanical properties and phosphorescence properties in ionic gels.

Method used

Using a method based on anion-induced phase separation strategy, an organic ion gel with high ion conductivity, stretchability and long phosphorescence lifetime was prepared by configuring a polymer ion solution containing hydroxyl groups and a luminescent group solution, adding inorganic salts, and freeze-thawing and low-temperature drying.

Benefits of technology

It achieves high ionic conductivity (≥1S/m), long phosphorescence life (≥100ms) and stretchability (≥400%), and has excellent environmental tolerance and recyclability, and is suitable for applications such as electronic skin and encrypted keyboards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775591A_ABST
    Figure CN119775591A_ABST
Patent Text Reader

Abstract

The invention discloses full-color organic ionic gel with high ionic conductivity, stretchability and long phosphorescence lifetime based on an anion-induced phase separation strategy and application of the full-color organic ionic gel. A method comprises the steps that anions are introduced into a polymer ionic solution containing a large number of hydroxyl groups, and molecular chain rearrangement is induced through freeze thawing and low-temperature drying, so that the full-color organic ionic gel with the high ionic conductivity, the stretchability and the long phosphorescence lifetime is obtained; an ionic liquid enrichment area and a polymer enrichment area are constructed, the highly solvated ionic liquid enrichment area is a soft phase and bears elastic deformation and ion transmission functions, and the polymer enrichment area is a hard phase and bears mechanical load and induces phosphorescence emission. The problems that an existing phosphorescent material is poor in mechanical property, cannot be stretched and is short in phosphorescent service life are solved, and the mechanical property and phosphorescent property of the ionic gel are synergistically improved. The prepared ionic gel has excellent environmental tolerance, recoverability and stimuli responsiveness; and multicolor phosphorescent display and responsive electric signals can be used for constructing a soft robot and an information encryption device for dual-channel information interaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a phosphorescent material with stretchability, and in particular to an organic ion gel with high ionic conductivity, stretchability and long phosphorescence life based on an anion-induced phase separation strategy, and the preparation and application thereof. Background Art

[0002] Most traditional room temperature phosphorescent materials are inorganic, such as rare earth materials, which are high in cost, highly toxic, and have limited application range. In recent years, organic phosphorescent materials have attracted widespread attention due to their advantages such as excellent processability and low toxicity. Among them, in order to achieve efficient phosphorescent emission, constructing a rigid polymer network to fix the triplet state of the luminescent group is a common strategy. As a result, most phosphorescent materials are rigid, brittle materials with no deformation ability. In response to the above problems, strategies such as self-assembly and polymerization-induced crystallization are used to construct elastic hydrogels with room temperature phosphorescent properties. However, it still has disadvantages such as easy evaporation of water and low temperature resistance. Ion gel is a material system with polymer as a three-dimensional network structure and ionic liquid as a solvent. It has the advantages of non-volatility, flame retardancy, and high ionic conductivity, and has attracted widespread attention. On this basis, the construction of ion gels with long phosphorescent lifetime and excellent mechanical properties is of great significance for the next generation of bionic robots, human-computer interaction and other fields. However, the above goals are not easy to achieve because the rigid structure required for long phosphorescent lifetime is inconsistent with the natural flexibility of ion gels. There is an urgent need for a technical means to achieve a synergistic improvement in both mechanical and phosphorescent properties in ion gels. Summary of the invention

[0003] The purpose of the present invention is to provide an organic ion gel with high ionic conductivity, stretchability and long phosphorescence life based on an anion-induced phase separation strategy, as well as its preparation and application, to solve the problems of poor mechanical properties, non-stretchability and short phosphorescence life of existing phosphorescent materials, while achieving the purposes of high ionic conductivity (≥1S / m), environmental tolerance, recyclability, long phosphorescence life (≥100ms) and stretchability (≥400%), and to construct electronic skin and encryption keyboard based on dual-channel interaction of color and electrical signals by using multi-color phosphorescence imaging and stimulus-responsive electrical signals.

[0004] In order to achieve the above object, the present invention provides a method for preparing a stretchable phosphorescent material, the method comprising:

[0005] (1) preparing a polymer ion solution containing hydroxyl groups, adding a luminescent group solution after the solution is clarified, and adding an inorganic salt and stirring until the solution is clear to obtain a precursor solution; the polymer containing hydroxyl groups is any one or more of cellulose, chitosan, cellulose derivatives, polyvinyl alcohol, polyacrylic acid and polymethacrylic acid; the ionic liquid is any one or more of 1-ethyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium bromide or 1-ethyl-3-methylimidazolium acetate, 1-allyl-3-methylimidazolium chloride and 1-butyl-3-methylimidazolium chloride; the luminescent group is any one or more of isothiocyanate, rhodamine, pyrene tetracarboxylic anhydride, polyacrylic acid, polyacrylamide, naphthalene dicarboxylic anhydride and pyrene butyric acid; the inorganic salt is any one or more of sodium carbonate, sodium sulfate, trisodium citrate, sodium chloride, potassium chloride and potassium sulfate. The concentration of the inorganic salt is 0.1% to 2%, and the mass ratio of the ionic liquid, the luminescent group solution and the inorganic salt is (10 to 100):1:1.

[0006] (2) The precursor solution is freeze-thawed and low-temperature dried to obtain an organic ion gel.

[0007] Preferably, in the polymer ion solution containing hydroxyl groups, the concentration of the polymer solution containing hydroxyl groups is 0.1% to 15%, and the mass ratio of the polymer solution containing hydroxyl groups to the ionic liquid is 100:(1 to 99).

[0008] Preferably, the concentration of the luminescent group solution is 0.1% to 5%. With the increase of inorganic salts, the toughness and stress of the ion gel increase, but excessive inorganic salts will reduce the toughness and stress of the ion gel.

[0009] Preferably, the polymer containing hydroxyl groups is polyvinyl alcohol, the ionic liquid is 1-ethyl-3-methylimidazolium chloride, the luminescent group is polyacrylamide, and the inorganic salt is sodium chloride.

[0010] Preferably, the mass ratio of the polymer containing hydroxyl groups to the solvent in the polymer solution containing hydroxyl groups is (0.1-1):10.

[0011] Preferably, the freeze-thaw temperature is -30°C to 0°C; the drying temperature is 40°C to 80°C; and the drying time is 0.1h to 12h.

[0012] The present invention provides a stretchable phosphorescent material obtained by the preparation method described above.

[0013] Preferably, the stretchable phosphorescent material has a microphase separation structure.

[0014] The present invention provides an application of the stretchable phosphorescent material as described above in the preparation of electronic skin, anti-counterfeiting patterns and stress-strain sensors.

[0015] Preferably, the application comprises wearable electronics.

[0016] The present invention proposes an organic ion gel with high ionic conductivity, stretchability and long phosphorescence life based on anion-induced phase separation strategy, and its preparation and application, which solves the problems of poor mechanical properties, non-stretchability and short phosphorescence life of existing phosphorescent materials, and has the following advantages:

[0017] 1. The construction of stretchable room temperature phosphorescent ion gel was realized. In addition to high ionic conductivity (≥1S / m), the phosphorescence lifetime exceeded 110ms, the tensile strength reached 9MPa, and the elongation at break exceeded 400%;

[0018] 2. It has excellent environmental tolerance and still has high elasticity (elongation at break exceeding 300%) and phosphorescent emission properties at sub-zero temperatures.

[0019] 3. It can be processed repeatedly and still has excellent phosphorescence performance, and the phosphorescence life does not decay. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the phosphorescence image of Example 1 of the present invention under stretching conditions.

[0021] Figure 2 These are SEM images of the gels of Examples 1-2 of the present invention and Comparative Examples 1-2.

[0022] Figure 3 It is the stress diagram of the gel of Examples 1-2 of the present invention and Comparative Examples 1-3.

[0023] Figure 4 The phosphorescence lifetime diagrams of the gels of Examples 1-2 of the present invention and Comparative Examples 1-2 are shown.

[0024] Figure 5 These are the full-color phosphorescent images of Examples 1 and 3 of the present invention.

[0025] Figure 6 This is the phosphorescence image of Example 3 of the present invention under stretching conditions.

[0026] Figure 7 This is a diagram of the mechanical properties of Example 1 and Example 3 of the present invention at low temperature (-20°C).

[0027] Figure 8 The phosphorescence images before and after recovery of Example 1 and Example 3 of the present invention are shown.

[0028] Fig. 9 This is the response of the gel in Example 1 of the present invention to external stimuli at room temperature.

[0029] Fig.10 This is a diagram showing the application of the gel in Example 4 of the present invention.

[0030] Fig.11 This is a diagram showing the application of the gel in Example 5 of the present invention.

[0031] Fig.12 The conductivity diagrams of the gels of Examples 1 to 2 of the present invention and Comparative Examples 1 to 3 are shown.

[0032] Fig.13 The graphs are toughness and tensile strength of the gels of Examples 1 to 2 of the present invention and Comparative Examples 1 to 3. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] The sources of the reagents involved in the following examples are as follows:

[0035] Polyvinyl alcohol (PVA-1799) (degree of polymerization 1700, degree of alcoholysis 99%), polyacrylamide (PAM), N,N-dimethylformamide (DMF) and methyl sulfoxide (DMSO) were purchased from Chengdu Kreiklin Chemical Co., Ltd.

[0036] Sodium chloride (NaCl) (purity 99.5%), 1-ethyl-3-methylimidazolium chloride, and 1,8-naphthalene dicarboxylic anhydride (1,8-NA) were purchased from Shanghai MacLean Biochemical Co., Ltd. (China).

[0037] 1-Pyrenebutyric acid (PyBA) was purchased from Shanghai Haohong Science Co., Ltd.

[0038] Example 1

[0039] A method for preparing an organic ion gel with high ionic conductivity, stretchability and long phosphorescence lifetime based on an anion-induced phase separation strategy, the method comprising:

[0040] (1) 2 g of polyvinyl alcohol (PVA) was dissolved in 10 mL of deionized water to obtain a PVA solution, 2 g of 1-ethyl-3-methylimidazolium chloride was added to the PVA solution, and after the solution was clarified, 2 mL of a 5% polyacrylamide (PAM) solution was added, and finally 0.3 g of sodium chloride was added and stirred until the solution became clear to obtain a precursor solution.

[0041] (2) The precursor solution was transferred to a tetrafluoroethylene mold, frozen and thawed at -20°C, and then kept in a 60°C forced air oven for 6 h to obtain an ion gel, which was recorded as PVA / PAM-NaIL 1 gel.

[0042] Example 2

[0043] A method for preparing an organic ion gel with high ionic conductivity, stretchability and long phosphorescence lifetime based on anion-induced phase separation strategy is basically the same as that in Example 1, except that:

[0044] In step (1), the amount of sodium chloride added was adjusted from 0.3 g to 0.5 g;

[0045] The same operation as in Example 1 was performed to obtain a gel named PVA / PAM-NaIL 2.

[0046] Comparative Example 1

[0047] The preparation method of an organic ion gel is basically the same as that of Example 1, except that:

[0048] In step (1), no sodium chloride is added;

[0049] The same operation as in Example 1 was performed to obtain a gel named PVA / PAM-IL.

[0050] Comparative Example 2

[0051] A method for preparing a room temperature phosphorescent film is substantially the same as that in Example 1, except that:

[0052] In step (1), 1-ethyl-3-methylimidazolium chloride is not added;

[0053] The same operation as in Example 1 was performed to obtain a thin film denoted as PVA / PAM-Na.

[0054] Comparative Example 3

[0055] The preparation method of an organic ion gel is basically the same as that of Example 1, except that:

[0056] In step (1), the amount of sodium chloride added was adjusted from 0.3 g to 0.6 g;

[0057] The same operation as in Example 1 was performed to obtain a gel named PVA / PAM-NaIL 3.

[0058] Example 3

[0059] A method for preparing an organic ion gel with high ionic conductivity, stretchability and long phosphorescence lifetime based on anion-induced phase separation strategy is basically the same as that in Example 1, except that:

[0060] In step (1), a 2 mL volume, 5% mass fraction polyacrylamide (PAM) solution is adjusted to a 2 mL volume, 5% mass fraction of o-aminobenzoic acid (NPA) or a 2 mL volume, 5% mass fraction of phenylbutyric acid (PyBA);

[0061] The same operation as in Example 1 was performed to obtain gels named PVA / NPA-NaIL and PVA / PyBA-NaIL.

[0062] Example 4

[0063] The preparation method of a dual-signal pathway soft robot motion monitoring material is basically the same as that in Example 1, except that:

[0064] Through the same operation as in Example 1, the obtained gels were respectively encapsulated with polydimethylsiloxane (PDMS) and then pasted on the joints of the soft robot manipulator.

[0065] Example 5

[0066] The preparation method of an anti-counterfeiting encryption keyboard is basically the same as that of Example 1, except that:

[0067] Through the same operation as in Example 1, the obtained gels were placed in molds, kept at 100° C. and 5 kPa pressure for 1 hour, packaged with PDMS, and connected with wires.

[0068] SEM characterization of experimental example 1 materials

[0069] The gels of Examples 1-2 of the present invention and Comparative Examples 1-2 were characterized by SEM, and the morphology of the ion gels was studied using a 10.0 kV field emission SEM (ZEISS GeminiSEM 360).

[0070] like Figure 2 As shown, the SEM images of the gels of Examples 1 to 2 of the present invention and Comparative Examples 1 to 2, wherein PVA / PAM-NaIL 1 is the gel prepared in Example 1; PVA / PAM-NaIL 2 is the gel prepared in Example 2; PVA / PAM-IL is the gel prepared in Comparative Example 1; PVA / PAM-Na is the gel prepared in Comparative Example 2, the blue part in the figure represents the polymer molecular chain enriched area, and the red part represents the ionic liquid enriched area. Figure 2 It can be seen that Examples 1 to 2 have obvious phase separation structures, while Comparative Examples 1 to 2 have no obvious microphase separation structures. This is because the introduction of salting-out anions can produce strong interactions with PVA molecular chains, inducing the formation of hydrogen bonds between PVA molecular chains on the one hand, and excluding free ionic liquids from the molecular chain-enriched region on the other hand, forming a unique microphase separation structure.

[0071] Experimental Example 2 Mechanical Properties of Materials

[0072] The mechanical properties of the gels of Examples 1 to 2 of the present invention and Comparative Examples 1 to 2 were characterized, and the tensile properties were tested at room temperature using a universal testing machine (UTM-4103, China). The hydrogels were cut into rectangular samples (50 mm × 10 mm × 2 mm) and measured at a strain rate of 10 mm / min. The sample length between the clamps was initially 30 mm. The tensile modulus of the hydrogel was calculated based on the slope of the stress-strain curve at 5% to 15% strain, and the area enclosed by the stress-strain curve is the toughness of the hydrogel.

[0073] like Figure 3 As shown, the stress diagrams of the gels of Examples 1 to 2 and Comparative Examples 1 to 3 of the present invention, wherein PVA / PAM-NaIL 1 is the gel prepared in Example 1; PVA / PAM-NaIL 2 is the gel prepared in Example 2; PVA / PAM-IL is the gel prepared in Comparative Example 1; PVA / PAM-Na is the gel prepared in Comparative Example 2; and PVA / PAM-NaIL 3 is the gel prepared in Comparative Example 3. Figure 3 It can be seen that the tensile strength of the gel PVA / PAM-NaIL 2 of Example 2 of the present invention is greater than 9MPa when the elongation at break is about 430%. Moreover, the elongation at break and toughness of Examples 1-2 are significantly higher than those of Comparative Examples 1-2. This is because in the microphase separation structure, the ionic liquid-enriched region is highly solvated, has a large free volume, and macroscopically exhibits a three-dimensional network structure with elastic deformation ability; while the polymer chain-enriched region has a small free volume due to the presence of multiple hydrogen bonds, and macroscopically exhibits a hard phase, which can be used as an energy-bearing unit, thereby improving the mechanical properties of the ion gel. Comparative Examples 1-2 without a microphase separation structure have no effective energy-bearing unit and poor mechanical properties. And the stress and strain of Comparative Example 3 using an excessive amount of inorganic salt both decrease.

[0074] like Fig.13 As shown in the figure, the toughness and tensile strength of the gels of Examples 1 to 2 of the present invention and Comparative Examples 1 to 3, wherein PVA / PAM-NaIL 1 is the gel prepared in Example 1; PVA / PAM-NaIL 2 is the gel prepared in Example 2; PVA / PAM-IL is the gel prepared in Comparative Example 1; PVA / PAM-Na is the gel prepared in Comparative Example 2; and PVA / PAM-NaIL 3 is the gel prepared in Comparative Example 3. Fig.13 It can be seen that with the increase of inorganic salts, the toughness and stress of ion gel are increasing. However, excessive inorganic salts will reduce the toughness and stress of ion gel.

[0075] like Figure 7As shown in the figure, the mechanical properties of Example 1 and Example 3 of the present invention at low temperature (-20°C), wherein PVA / PAM-NaIL 1 is the gel prepared in Example 1; PVA / PAM-IL is the gel prepared in Comparative Example 1; and PVA / PAM-Na is the gel prepared in Comparative Example 2. Figure 7 It can be seen that the gel prepared in Example 1 of the present invention has a straight-chain polymer as the main chain, namely PVA (polyvinyl alcohol), at low temperature (-20°C). The obtained material has high-strength and high-toughness mechanical properties (elongation at break is about 340%, and tensile strength is 7.5 MPa), becoming a stretchable material.

[0076] Phosphorescence lifetime of materials in Experimental Example 3

[0077] The phosphorescence lifetime of the gels of Examples 1-2 of the present invention and Comparative Examples 1-2 was characterized by using a FLS-980 photoluminescence spectrometer (Edinburgh Instruments, UK) for measurement, with the excitation wavelength being 365 nm.

[0078] like Figure 1 As shown in FIG. 1 , the phosphorescence image of Example 1 of the present invention under stretching conditions. Figure 1 It can be seen that the ion gel has obvious blue phosphorescence after being irradiated by 365nm ultraviolet light when stretched.

[0079] like Figure 4 As shown, the phosphorescence lifetime diagrams of the gels of Examples 1 to 2 of the present invention and Comparative Examples 1 to 2, wherein PVA / PAM-NaIL 1 is the gel prepared in Example 1; PVA / NPA-NaIL and PVA / PyBA-NaIL are the gels prepared in Example 3. Figure 4 It can be seen that the RTP lifetime of PVA / PAM-NaIL ion gel increased significantly, among which the increase of PVA / PAM-NaIL 2 was the most obvious, and its lifetime was the longest, reaching 112.4 milliseconds.

[0080] like Figure 5 As shown, the full-color phosphorescence images of Example 1 and Example 3 of the present invention. Figure 5 It can be seen that the phosphorescence lifetime of Examples 1 to 2 of the present invention is significantly higher than that of Comparative Examples 1 to 2. This is because in the microphase separation structure, the polymer chain-rich region with highly aggregated molecular chains and obvious rigidity characteristics can produce aggregation-induced emission, and at the same time, this rigid structure can effectively fix the triplet state of the luminescent group and increase the phosphorescence lifetime.

[0081] like Figure 6 As shown in FIG. 3 , the phosphorescence image of Example 3 of the present invention under stretching conditions. Figure 6 It can be seen that PVA / NPA-NaIL and PVA / PyBA-NaIL ion gels can maintain bright ultra-long room-temperature phosphorescence under different strain conditions.

[0082] like Figure 8 As shown, the phosphorescence images before and after recovery of Example 1 and Example 3 of the present invention, wherein PVA / NPA-NaIL and PVA / PyBA-NaIL are gels prepared in Example 3, and PVA / PAM-NaIL is the gel prepared in Example 1; UV on means the UV light is turned on, and UV off means the UV light is turned off. Figure 8 It can be seen that PVA / PAM-NaIL, PVA / NPA-NaIL and PVA / PyBA-NaIL ion gels have good recyclability after hot pressing. After one cycle, the full-color afterglow can be easily identified by the naked eye.

[0083] Experimental Example 4 Electrical conductivity of materials

[0084] The conductivity of the gels of Examples 1 to 2 of the present invention and Comparative Examples 1 to 2 was tested by an electrochemical workstation (CHI760E, China Chenhua) with an applied voltage of 1 V and a frequency of 1 kHz. The size of the tested rectangular hydrogel sample was 50 mm × 10 mm × 2 mm. The conductivity (σ) was calculated by the following formula:

[0085]

[0086] where R is the measured resistance, L is the length, and A is the cross-sectional area of ​​the hydrogel sample.

[0087] like Fig.12 As shown, the conductivity diagrams of the gels of Examples 1 to 2 of the present invention and Comparative Examples 1 to 3, wherein PVA / PAM-NaIL 1 is the gel prepared in Example 1; PVA / PAM-NaIL 2 is the gel prepared in Example 2; PVA / PAM-IL is the gel prepared in Comparative Example 1; PVA / PAM-Na is the gel prepared in Comparative Example 2; and PVA / PAM-NaIL 3 is the gel prepared in Comparative Example 3. Fig.12 It can be seen that the ionic conductivity of the gel PVA / PAM-NaIL 2 prepared in Example 2 of the present invention is 1.04 S / m, which is higher than that of PVA / PAM-NaIL 1 and PVA / PAM-NaIL 3, and is not much different from the conductivity of the gel PVA / PAM-IL prepared in Comparative Example 1.

[0088] Experimental Example 5: External stimulus response and application demonstration of materials

[0089] The gel of Example 1 of the present invention was subjected to external stimulation at room temperature. Specifically, an electrochemical workstation (CHI760E, Chenhua, China) was used to record the external electrical signal of the PVA-based ion gel under external stimulation. The applied voltage was 1 V and the frequency was 1 kHz. In order to continuously measure the resistance during the stretching process, the ion gel was fixed on a self-made stretching table with electrical conductors at both ends.

[0090] like Fig. 9 As shown in the figure, the response of the gel in Example 1 of the present invention to external stimuli at room temperature, where A is the resistance (ΔR / R 0 ) relative change with increasing strain. The results show that the resistance of PVA / PAM-NaIL ion gel can accurately and reversibly respond to various strains (10% to 100%); B is the linear relationship between strain and electrical signal, with a correlation coefficient of 0.995; C is a stable and reliable relative resistance change under a compression condition of 15kPa; D is the relative resistance change corresponding to different degrees of finger bending (30°, 60° and 90°) detected by PVA / PAM-NaIL ion gel; E is the relative resistance change corresponding to wrist bending detected by PVA / PAM-NaIL ion gel; F is the relative resistance change corresponding to human walking detected by PVA / PAM-NaIL ion gel. Fig. 9 It can be seen that PVA / PAM-NaIL ion gel can obtain stable electrical signals under different deformation conditions, which shows that ion gel has excellent reliability when used in intelligent mechanical conduction devices.

[0091] The gels of Examples 4 to 5 of the present invention were applied for demonstration. The specific method is that the present invention places stretchable PVA-based ion gels of different phosphorescent colors at the joints of the robot hand. Different phosphorescent colors can provide additional position information, for example, red represents the thumb area, green represents the index finger, and blue represents the middle finger. By identifying the color image of the "finger" during movement, the gesture information of the robot hand can be preliminarily obtained.

[0092] like Fig.10 As shown, the application display diagram of the gel of Example 4 of the present invention, wherein A is the phosphorescence display deformation, electrical signal change and gesture change of grabbing a ball; B is the phosphorescence display deformation, electrical signal change and gesture change of grabbing paper; C is the phosphorescence display deformation, electrical signal change and gesture change of grabbing a cylinder. Fig.10 It can be seen that the ultra-long afterglow and bright room-temperature phosphorescence color of the ion gel are easily recognized by the naked eye. Combined with electrical signals, users can more intuitively and accurately identify the body language information of the soft robot.

[0093] The present invention uses the stretchable Example 5 gel to make a keyboard.

[0094] like Fig.11 As shown, the application display diagram of the gel of Example 5 of the present invention. Fig.11It can be seen that when the ultraviolet excitation stops, the keyboard switches to encryption mode and specific information is encoded in different room temperature phosphorescent colors. The relative change in resistance when the key is pressed can be used as a transmission signal. The keyboard can only be unlocked by correctly pressing the keys marked with "blue" phosphorescent letters, which will generate the necessary electrical signals. Otherwise, it will be regarded as a false touch and the information cannot be transmitted. The vowels A, E, I, O and U appear as "red" phosphorescence on the keyboard because they are very important when spelling words. If the electrical signals from these keys are detected before the keyboard is unlocked, an alarm will be triggered.

[0095] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A method for preparing an organic ion gel with high ionic conductivity, stretchability and long phosphorescence lifetime based on anion-induced phase separation strategy, characterized in that: The method includes: (1) preparing a polymer ion solution containing a hydroxyl group, adding a luminescent group solution after the solution becomes clear, and adding an inorganic salt and stirring until the solution becomes clear to obtain a precursor solution; The polymer containing hydroxyl groups is any one or more of cellulose, chitosan, cellulose derivatives, polyvinyl alcohol, polyacrylic acid and polymethacrylic acid; The ionic liquid is any one or more of 1-ethyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium bromide or 1-ethyl-3-methylimidazolium acetate, 1-allyl-3-methylimidazolium chloride and 1-butyl-3-methylimidazolium chloride; The luminescent group is any one or more of isothiocyanate, rhodamine, pyrene tetracarboxylic anhydride, polyacrylic acid, polyacrylamide, naphthalene dicarboxylic anhydride and pyrene butyric acid; The inorganic salt is any one or more of sodium carbonate, sodium sulfate, trisodium citrate, sodium chloride, potassium chloride and potassium sulfate; The concentration of the inorganic salt is 0.1% to 2%, and the mass ratio of the ionic liquid, the luminescent group solution and the inorganic salt is (10 to 100): 1: 1; (2) The precursor solution is freeze-thawed and dried to obtain an organic ion gel.

2. The preparation method according to claim 1, characterized in that: In the polymer ion solution containing hydroxyl groups, the concentration of the polymer solution containing hydroxyl groups is 0.1% to 15%, and the mass ratio of the polymer solution containing hydroxyl groups to the ionic liquid is 100:(1 to 99).

3. The preparation method according to claim 2, characterized in that: The concentration of the luminescent group solution is 0.1% to 5%.

4. The preparation method according to claim 1, characterized in that: The polymer containing hydroxyl groups is polyvinyl alcohol, the ionic liquid is 1-ethyl-3-methylimidazolium chloride, the luminescent group is polyacrylamide, and the inorganic salt is sodium chloride.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the polymer containing hydroxyl groups to the solvent in the polymer solution containing hydroxyl groups is (0.1-1):

10.

6. The preparation method according to claim 1, characterized in that: The freezing and thawing temperature is -30°C to 0°C; The drying temperature is 40° C. to 80° C.; the drying time is 0.1 h to 12 h.

7. A stretchable phosphorescent material obtained by the preparation method according to any one of claims 1 to 6.

8. The stretchable phosphorescent material according to claim 1, characterized in that: The stretchable phosphorescent material has a microphase separation structure.

9. Use of the stretchable phosphorescent material as claimed in claim 7 in the preparation of electronic skin, anti-counterfeiting patterns and stress-strain sensors.

10. The use according to claim 9, characterized in that: Such applications include wearable electronics.